(untitled) (GANIT: Journal of Bangladesh Mathematical Society, 2016)
The Tower of Hanoi is a popular mathematical puzzle, which appeared in 1885. During the past years, the problem has seen many variations. This paper reviews the Tower of Hanoi and its different variants. Some 3-peg variants are given in §2, §3 treats some 4-peg variants, §4 deals with the multi-peg generalization, and §5 gives some open problems GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 145-163